Bukti-Bukti Otentik Alkitab Sebagai Firman Allah: Suatu Kajian Bibliologi - L. M., Yusuf; L. Marriba, Narsing; Y. Sanderan, Manna (JURNAL LUXNOS, 2025)
In the postmodern era, the absoluteness and authority of the Bible as the Word of God have declined in the defense of the Christian faith. This is fueled by the convenience of the digital world, which is considered capable of meeting human needs, resulting in the Bible often being placed in a complementary position, rather than as the absolute and authoritative basis for church doctrine. This analysis concludes that the evidence within the Bible itself including divine inspiration, historical providence, and confirmation by Jesus Christ is overwhelming and absolute enough to answer the claim that the Bible is the Word of God and the source of eternal salvation. As Calvin asserted, the Bible is a Scripture that declares its own authenticity.